Occupational complexity and risk of Parkinson's disease - Valdés, Elise G; Andel, Ross; Sieurin, Johanna; Feldman, Adina L; Edwards, Jerri D; Långström, Niklas; Gatz, Margaret; Wirdefeldt, Karin (PloS one, 2014)
BACKGROUND: The etiology of Parkinson's disease (PD) remains unclear, and environmental risk-factors such as occupation have attracted interest. OBJECTIVE: The goal was to investigate occupational complexity in relation to PD. METHODS: We conducted a population-based cohort study based on the Swedish Twin Registry that included 28,778 twins born between 1886 and 1950. We identified 433 PD cases during the study period. Data on occupation were collected from either the 1970 or 1980 Swedish census, and occupational complexity was assessed via a job exposure matrix. Cox proportional hazard regression analyses with age as the underlying time scale were used to assess PD risk as a function of the three domains of occupational complexity: data, people, and things. Sex and smoking were included as covariates. Analyses stratified by twin pair were conducted to test for confounding by familial factors. RESULTS: High occupational complexity with data and people was associated with increased risk overall (Hazard Ratio [HR] = 1.07, 95% confidence interval [CI] 1.02-1.14, and HR = 1.10, 95% CI 1.01-1.21, respectively), and in men (HR = 1.08, 95% CI 1.01-1.16, and HR = 1.15, 95% CI 1.03-1.28, respectively). Complexity with things was not associated with risk of PD. When the analyses were stratified by twin pair, the HRs for occupational complexity with data and people were attenuated in men. CONCLUSIONS: High complexity of work with data and people is related to increased risk of PD, particularly in men. The attenuation of risk observed in the twin pair-stratified analyses suggests that the association may partly be explained by familial factors, such as inherited traits contributing to occupational selection or other factors shared by twins.
Keywords: Occupational Exposure; Registries; Cohort Studies; Sweden; rizikové faktory; Švédsko; Humans; lidé; kohortové studie; Parkinson Disease; pracovní expozice; registrace; Risk Factors; Parkinsonova nemoc